“Wax-sealed” theranostic nanoplatform for enhanced afterglow imaging-guided photothermally triggered photodynamic therapy - Liu, Gongyuan (2020)
Herein, persistent luminescence nanoparticles (PLNPs) and photosensitizer are integrated for cancer theranostics with high specificity and without the need of continuous illumination. Specifically, ZnGa1.996O4:Cr0.004 (PLNPs) and IR780 (photosensitizer) are encapsulated by a temperature‐responsive “wax‐seal” composed of oleic acid and hexadecanol. The seal prevents luminescence quenching and premature initiation of photodynamic therapy (PDT), until it is melted down by heat stimulus. After photothermal activation, the near‐infrared afterglow offered by PLNPs provides imaging with high signal‐to‐background ratio because of the absence of tissue autofluorescence, as well as continuously excited photosensitizer for reactive oxygen species generation. Such theranostic nanoplatform offers multimodal imaging–guided localized cancer PDT.